AVIATION AND TOURISM: IMPACT OF AVIATION ON THE TOURISM DEVELOPMENT OF UZBEKISTAN - Mukhayyo Khamroeva (Galaxy International Interdisciplinary Research Journal, 2022)
Tourism and aviation regularly interact with each other. These industries play an important role in the country’s economy, as both of them create a large number of jobs and generate an income stream to the country’s economy. The valuable and dynamic interaction of these two aspects of the economy can lead to the country’s economic growth. Although air transport and tourism are interdependent sectors, there is little research on their interaction (Spasojevich et al., 2017). In addition, it is important to indicate the impact of aviation on development of tourism.